1986
DOI: 10.1207/s15327752jpa5001_14
|View full text |Cite
|
Sign up to set email alerts
|

The Separation-Individuation Test of Adolescence

Abstract: The procedures undergone to establish the validity of the Separation- Individuation Test of Adolescence (SITA) are described. The test consists of six scales designed to measure key dimensions of adolescent separation-individuation. Each scale was subjected to three stages of validation: theoretical-substantive, internal-structural, and external-criterion. The results of data with 305 adolescents are reported. Although particular modifications from the original form are planned, appreciative levels of validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Higher scores indicate greater autonomy difficulties. On par with previous reports (Eggert, 2007; Levine et al, 1986), Cronbach’s alpha for the Separation Anxiety sub-scale was .66 to .77 across sex and pubertal groups.…”
Section: Methodssupporting
confidence: 77%
“…Higher scores indicate greater autonomy difficulties. On par with previous reports (Eggert, 2007; Levine et al, 1986), Cronbach’s alpha for the Separation Anxiety sub-scale was .66 to .77 across sex and pubertal groups.…”
Section: Methodssupporting
confidence: 77%
“…With regard to external validity, Levine et al (1986) found that subjects categorized as anxious-moody according to the Millon Adolescent Personality Inventory (MAPI; Millon, Green, & Meagher, 1982) achieved higher scores on the SITA Separation Anxiety subscale than other groups formed through MAPI classifications. Likewise, subjects in the confident-outgoing group (MAPI classification) scored higher than subjects in the other personality categories on the Healthy Separation subscale of the SITA (Levine et al, 1986). Reliability estimates for the SITA subscales have not yet been reported in the literature.…”
Section: Procedures and Instrumentationmentioning
confidence: 99%
“…Promising measurement strategies have recently been introduced. These include scales or subscales from the Separation Anxiety Test (SAT;Hamburg, 1972Hamburg, , 1980, the Psychological Separation Inventory (PSI; Hoffman, 1984), and the Separation-individuation Test of Adolescence (SITA; Levine, Green, & Millon, 1986). Grounded in psychoanalytic and neopsychoanalytic theory, the SAT is a semistructured, projective instrument that is commonly used to explore the link between adolescents' separation experiences and later emotional problems.…”
mentioning
confidence: 99%
“…Family distance regulation was measured with two scales that were revised for this project. The first was the Healthy Separation subscale from the Separation Individuation Test for Adolescence (Levine, Green, & Millon, 1986). This subscale was designed to measure an adolescent's sense of self within relationships with parents.…”
Section: Methodsmentioning
confidence: 99%
“…The reliability of the separatedness subscale in this study was low for both mothers and children. It could be that the items included from the healthy separation subscale of the Separation Individuation Test for Adolescents (Levine et al, 1986) are not relevant for mothers and their younger children, or that a five-item scale with these particular items did not provide enough internal consistency. More work is needed to develop measures of family distance regulation that are sensitive to change, and appropriate for children and adolescents.…”
Section: Limitationsmentioning
confidence: 99%